THE THEORY OF CHINESE ONOMATOPOEIA: A LINGUISTIC EXPLORATION (Journal of Universal Science Research, 2026)
Onomatopoeia, the art of imitating natural sounds through language, offers a fascinating glimpse into how human cognition interacts with the auditory world. Chinese onomatopoeia, in particular, stands out due to its rich and vibrant expressions that beautifully encapsulate sounds from nature, animals, and human activities. In this article, we delve into the theory behind Chinese onomatopoeia and its significance in linguistic studies.